Synthesis of nanostructured LiCoO2 AS cathode material for lithium-ion batteries - Mamyrbaeva, Y.Y.; Hobosyan, M.A.; Kumekov, S.E.; Martirosyan, K.S. (Publishing House of the KarSU named after E.A.Buketov, 2013)
Nanostructured LiCoO2 powders were prepared by Carbon combustion synthesis of oxide method using carbon as starting materials. The thermo-gravimetric analysis was used to identify interaction features in the system LiNO3 - Co3O4 – Carbon to produce LiCoO2. X-ray diffraction showed that the as-synthesised product were single phase. The crystalline nanoparticles synthesized were nearly spherical, and their average particle diameters ranged from 60 to 200 nm. Cyclic voltammetry and charge-discharge experiments were applied to characterize the electrochemical properties of the powders as cathode materials for lithium-ion batteries. The cyclic voltammogram curves indicated faster diffusion and migration of Li+ cations in the nanostructured LiCoO2 electrode. In the first charge-discharge process, the material showed the capacity of 200 (mAh)/g.
Keywords: Carbon Combustion Synthesis of Oxide (CCSO); Lithium Cobaltate; Nanoparticles; Li-ion Rechargeable Batteries